Spatially diverse hydroclimatic response to the 4.2 ka event in the Asian monsoon region. (15th November 2022) - Lin, Jie; Jiang, Wenying; Wang, Luo; Zhang, Enlou; Tang, Lingyu; Yang, Xiaoxiao; Chu, Guoqiang; Yang, Shiling; Xiao, Jule
Abstract: The 4.2 ka event was a widespread abrupt cooling event in the Northern Hemisphere. However, there was a spatially inconsistent hydroclimatic response to the 4.2 ka event in the Asian monsoon region. To further characterize and to determine the origin of this phenomenon, we present a pollen record spanning the interval from 10.7 ka to the present from a subalpine lake in the Hengduan Mountains, southwestern China, which are climatically influenced by the Indian monsoon; and we then reconstruct the spatial pattern of the hydroclimatic response to the 4.2 ka event across the Asian monsoon region, based on a synthesis of our own and previously published data. The results reveal the following. (i) During the interval of 4.5–3.9 ka (spanning the 4.2 ka event) in the subtropical mountains there were abrupt decreases in evergreen broadleaved trees, including evergreen Quercus, Castanopsis and Cyclobalanopsis . (ii) The hydroclimatic response to the 4.2 ka event across the Asian monsoon region was characterized by a tripolar precipitation pattern, with decreased rainfall over India and southwestern and northern China, and increased rainfall over central China. Therefore, we conclude that the hydroclimatic response to the 4.2 ka event in the Asian monsoon region was spatially heterogenous, which we argue was related to the slowdown of the Atlantic Meridional Overturning Circulation (AMOC). During the interval of 4.5–3.9 ka, cooling at high latitudes of the Northern Hemisphere, caused by AMOC weakening, led to the southward movement of the Intertropical Convergence Zone (ITCZ), which resulted in decreased rainfall over most of the Asian monsoon region. The wet conditions in central China may have been modulated by the southward movement of the westerlies, which was also caused by the cooling at northern high latitudes. The southward displacement of the westerlies restricted the northward penetration of the monsoonal air flow, and thus the monsoon rainbelt stagnated over central China, where there was a corresponding increase in precipitation. Highlights: Evergreen broadleaved trees decreased between 4.5 and 3.9 ka in southwestern China. The change infers a shift to a cool and dry climate, coincident with the 4.2 ka event. Records of the 4.2 ka event from across the Asian monsoon region were synthesized. A tripolar Asian monsoon precipitation pattern occurred during the 4.2 ka event. The 4.2 ka event was related to the weakened Atlantic Overturning Circulation.